Comparison I-V Characteristics of Sb/c-Si and Al/c-Si Junction - Hachim, Fatin G.; Al-Ansari, Ramiz A.; AL-Lamy, Hussein Kh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Hetero junctions are fabricated by depositing antimony (Sb) and Al films on n-type single crystal(c-Si) wafers by the method of vacuum evaporation with thickness (0.25Âµm), with rate of deposition equals to 2.77 Ã…/sec, all samples are annealed in a vacuum for one hour at 473K. The tests have shown that all the films have polycrystalline structure for all Sb films. The barrier heights in (Sb/c-Si) junction was found to be equal 0.825eV, but(Al/c-Si) junction ohmic contact. Current-voltage measurements confirm this behaviour.